Core science 1 - Milner, Bryan; Martin, Jean.; Evans, Peter (b, 1998)
The pupil book Core Science 1 is one of two books for Key Stage 3 Science. The carefully controlled language level and extensive use of images make these resources accessible to most pupils. Each double page spread provides balance of illustrations, text and questions to support the introducation of new concepts.
Includes index
Keywords: Biology -- Juvenile literature; Physics -- Juvenile literature; Chemistry -- Juvenile literature